Farmers’ Awareness of Agricultural Environmental Risks in Kalabshaw and Zayan Area in Dakahlia Governorate - Gomaa, Aml Mohamed; Abou- Elnaga, Mohamed Ahmed; Moawad, Hamdi Mohamed (Journal of agricultural, environmental and veterinary sciences, 2021)
The research aimed to determine the level of farmers’ awareness about of agricultural environmental risks in new reclamation land association’s in kalabshaw and zayan region, in dakahlia governorate by determining the level of farmers’ awareness of causes of spread of agricultural environmental risks, as well as their awareness level of damage which caused by it, In addition to identify their awareness of spread rate agricultural environmental risks, and resulting damage from it, as well as the strengths, weaknesses, opportunities and challenges available to farmers to confront agricultural environmental risks in search area. The research was conducted on 337 farmers who were selected randomly and systematically from farmers of new reclamation landassociation’s in kalabshaw and zayan region. Data were collected by using a questionnaire, pretest was done until it became valid for collected data during March and April 2021. Morgan and Krejcie equation had been used to determine the sample size. Frequencies, percentages, rang, mean, standard deviation were used to present and analysis study data. The main results are as follows 1- More than two- fifths of farmers 42.4 % Their awareness level of reasons agricultural environmental risks spread was high.. 2- Two- fifths of farmers 40.7 % Their awareness level of awareness of damage which caused by agricultural environmental risks was high. 3- Two- fifths of farmers 40.4 % Their awareness level of diffusion rate agricultural environmental risks spread was high. 4- More than one- third of farmers 38.3 % Their awareness level of extent damage caused agricultural environmental risks spread was high 5- The most important aspects of strengths of farmers to face agricultural environmental risks were: Be careful to adjust dates of cultvited some crops, especially vegetables, to reduce sides effects of climate change 89%. 6- The most important aspects of weaknesses of farmers to face agricultural environmental risks were: Climate changes led to decrease productivity of some crops and increase food prices by 88.4%. 7- The most important aspects of opportunities of farmers to face agricultural environmental risks were: attuide towards to contract farming to prevent the exploitation of traders 89%. 8- The most important aspects of the challenges faced of farmers to face agricultural environmental risks were: The difficult economic conditions such as rise in land rent and rise prices of production requirements by 90.5%.